Leftward flow determines laterality in conjoined twins - Tisler, Matthias Konrad; Thumberger, Thomas (Current biology, 2017)
Summary. Conjoined twins fused at the thorax display an enigmatic left-right defect: although left twins are normal, laterality is disturbed in one-half of right twins [1, 2, 3]. Molecularly, this randomization corresponds to a lack of asymmetric Nodal cascade induction in right twins [4]. We studied leftward flow [5, 6] at the left-right organizer (LRO) [7, 8] in thoracopagus twins in Xenopus, which displayed a duplicated, fused, and ciliated LRO. Cilia were motile and produced a leftward flow from the right LRO margin of the right to the left margin of the left twin. Motility was required for correct laterality in left twins, as knockdown of dynein motor dnah9 prevented Nodal cascade induction. Nodal was rescued by parallel knockdown of the inhibitor dand5 [9, 10] on the left side of the left twin. Lack of Nodal induction in the right twin, despite the presence of flow, was due to insufficient suppression of dand5. Knockdown of dand5 at the center of the fused LRO resulted in asymmetric Nodal cascade induction in the right twin as well. Manipulation of leftward flow and dand5 in a targeted and sided manner induced the Nodal cascade in a predictable manner, in the left twin, the right one, both, or neither. Laterality in conjoined twins thus was determined by cilia-driven leftward fluid flow like in single embryos, which solves a century-old riddle, as the phenomenon was already studied by some of the founders of experimental embryology, including Dareste [11], Fol and Warynsky [12], and Spemann and Falkenberg [13] (reviewed in [14]).